Hybrid Book Integrating Rumah Tuo Local Wisdom for Civic Education: Buku Hybrid Berbasis Kearifan Lokal Rumah Tuo untuk Pendidikan Kewarganegaraan - Putri Nabila Rizki; Ahmad Susanto; Muhamad Sofian Hadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Civic Education learning in Elementary School Teacher Education programs remains dominated by conventional teaching materials that are insufficiently contextual and weakly connected to students’ socio-cultural realities. Specific Background: In the context of PGSD students, the local wisdom of Rumah Tuo, representing the cultural identity of the Batin Tribe in Jambi, contains civic values such as deliberation, mutual cooperation, unity, and social responsibility that are relevant to Civic Education learning. Knowledge Gap: Despite its educational potential, there is a lack of systematically developed and tested hybrid learning resources that integrate Rumah Tuo local wisdom into Civic Education for PGSD students. Aims: This study aims to develop a hybrid book based on the local wisdom of Rumah Tuo as a Civic Education learning resource for PGSD students and to examine its feasibility, practicality, and learning outcomes. Results: Using a Research and Development approach with the ADDIE model, the developed hybrid book was assessed as highly feasible by material, media, and language experts, considered practical by students, and demonstrated positive learning outcomes in understanding Civic Education values integrated with local wisdom. Novelty: The novelty of this study lies in the systematic integration of Rumah Tuo local wisdom into a hybrid textbook format specifically designed and tested for PGSD Civic Education learning. Implications: The hybrid book provides a contextual, innovative, and culturally grounded learning resource that supports Civic Education learning in higher education and contributes to the preservation of local cultural values in the digital learning environment. Highlights • The hybrid book embeds Rumah Tuo cultural values within Civic Education learning content• Expert validation and student trials confirm high feasibility and usability• Hybrid learning resources support contextual civic value understanding for PGSD students Keywords Hybrid Book; Local Wisdom; Rumah Tuo; Civic Education; PGSD